PEMBUATAN MIKROORGANISME LOKAL (MOL) BERBAHAN DASAR LIMBAH NASI UNTUK PROSES FERMENTASI PUPUK DAN PAKAN TERNAK DI DESA G1 MATARAM MUSI RAWAS - Marliza, Yayuk; Reza Riadi; Lilis Setiani (Fakultas Pertanian, 2024)
Local Micro Organisms (MOL) are fermented solutions made from various locally available resources, both plants and animals. MOL can be used as a fermentation mixture for making animal feed and organic fertilizer. In G1 Mataram Village, Musi Rawas Regency, there is a lot of rice plant waste, namely straw which has not been fully utilized by breeders to be processed into feed through fermentation with MOL solution. This activity aims to help the community utilize agricultural waste and household waste in the form of stale rice to become products with economic value. Activities include program outreach, determining target communities, namely home-scale farmers, training and mentoring as well as program monitoring and evaluation. Through this program, public knowledge increases regarding the use of waste into animal feed and liquid organic fertilizer which has useful and selling value.